From Program to Performance Budgeting : The Challenge for Emerging Market Economies - Diamond, Jack (IMF Working Papers; Working Paper ;, 2003)
Many emerging market economies are trying to improve their budget processes and move to performance-based budgeting. This paper first reviews the evolution of the "new" performance budgeting model, increasingly being applied in industrial countries. By identifying its main components, the tasks faced by emerging market economies when converting their present budget systems to this model are determined. It is recognized that this conversion will not be easy and will require four major reform elements. First, any existing program structure must be set in the wider context of strategic budget planning and medium-term budget frameworks. Second, this typically involves redesigning and refining existing program structures. Third, existing budget-costing systems and associated skills will probably need to be improved. Fourth, and perhaps most difficult, a new system of accountability and budget incentives needs to be introduced. For emerging market economies, these should be viewed as the prerequisites for a successful introduction of the new performance-budgeting model.